PERAN SIKAP DALAM MEMEDIASI PENGARUH KESADARAN LINGKUNGAN TERHADAP NIAT BELI ULANG PRODUK MINUMAN KEMASAN HIJAU - Martana, I Made Yudi; Ardani, I Gst. A. Kt. Sri (E-Jurnal Manajemen, 2018)
Consumers who are sensitive to environmental conditions must have a good attitude to be aware of the environment so it will be easier for the emergence of the intention to buy back a green product in the future and maintain a positive attitude. This study was conducted on consumers who have ever purchased green beverage packaging products in the city of Denpasar. The method used to determine the sample is non-probability in the form of purposive sampling, the number of samples used in this study were as many as 120 respondents. The data were collected through questionnaires, interviews, and observations. The analysis technique used is path analysis and test of sobel. The results showed that: (1) environmental awareness has positive and significant impact on the role of attitude; (2) environmental awareness has a positive and significant impact on repurchase intention; (3) the role of attitudes has a positive and significant impact on repurchase intention; (4) attitudes act as a mediating variable between environmental awareness variables and repurchase intentions. Keywords : Role of Attitude, Environmental Awareness, repurchase intention